Improved estimation of cancer dependencies from large-scale RNAi screens using model-based normalization and data integration - James M. McFarland (Nature Portfolio, 2018)
Integrated analyses of multiple large-scale screenings can be complicated by batch effects and technical artefacts. McFarland et al. introduce DEMETER2, a hierarchical model coupled with model-based normalization, which allows the assessment of differential dependencies across genes and cell lines.